Coupled oxygen and dissolved inorganic carbon dynamics in coastal ocean and its use as a potential indicator for detecting water column oil degradation. (July 2016) - Hu, Xinping; Cai, Wei-Jun; Rabalais, Nancy N.; Xue, Jianhong
Abstract: Following the disastrous 2010 Deepwater Horizon oil spill, numerous studies have been carried out to investigate the impact of the oil spill on a variety of environments. However, it is currently unknown whether the spilled oil transported to the coastal ocean has caused any discernible perturbation to the inorganic chemistry of the water column. In this work we compared and contrasted a multiyear dataset (2006–2012) collected in the northern Gulf of Mexico continental shelf, an area subject to frequent summer hypoxia. Before and after the oil spill, apparent oxygen utilization (AOU) and dissolved inorganic carbon (DIC) in bottom water samples all showed consistent relationship that was close to Redfield reaction stoichiometry. However, we observed a possible oil degradation signal in the bottom waters during a July 2010 cruise as manifested by a significant deviation from all other years in the relationship between AOU and DIC. Based on stable carbon isotope analysis of bottom water DIC from a July 2011 cruise in the same region, oil carbon degradation in the water column was likely negligible and the shelf water had returned to the pre-spill conditions.